Differential diagnosis in orthopaedic oncology - Greenspan, Adam; Jundt, Gernot; Remagen, Wolfgang (Lippincott Williams & Wilkins, 2007)
This volume presents both the radiologist's and the pathologist's approach to differential diagnosis of musculoskeletal tumors and tumor-like lesions and details the radiologic and histopathologic features helpful in confirming a diagnosis. The book is illustrated with over 1,200 radiographs, CT and MR images, full-color photomicrographs, and schematic drawings. Tables list important diagnostic features, and schematic drawings summarize both radiologic and pathologic differential diagnoses.